Sex differences in the behavioral variant of frontotemporal dementia: A new window to executive and behavioral reserve. Issue 8 (16th February 2021) - Illán‐Gala, Ignacio; Casaletto, Kaitlin B.; Borrego‐Écija, Sergi; Arenaza‐Urquijo, Eider M.; Wolf, Amy; Cobigo, Yann; Goh, Sheng Yang M.; Staffaroni, Adam M.; Alcolea, Daniel; Fortea, Juan; Blesa, Rafael; Clarimon, Jordi; et al.
Abstract: Introduction: Biological sex is an increasingly recognized factor driving clinical and structural heterogeneity in Alzheimer's disease, but its role in the behavioral variant of frontotemporal dementia (bvFTD) is unknown. Methods: We included 216 patients with bvFTD and 235 controls with magnetic resonance imaging (MRI) from a large multicenter cohort. We compared the clinical characteristics and cortical thickness between men and women with bvFTD and controls. We followed the residuals approach to study behavioral and cognitive reserve. Results: At diagnosis, women with bvFTD showed greater atrophy burden in the frontotemporal regions compared to men despite similar clinical characteristics. For a similar amount of atrophy, women demonstrated better‐than‐expected scores on executive function and fewer changes in apathy, sleep, and appetite than men. Discussion: Our findings suggest that women might have greater behavioral and executive reserve than men, and neurodegeneration must be more severe in women to produce symptoms similar in severity to those in men.